The Effect Of Price, Product Quality, And Service Quality On Customer Satisfaction - Irawan, Kevin; Sitinjak , Tony (Action Research Literate, 2024)
The large number of online transportation users ultimately creates competition between online transportation service providers. Fast adaptation, affordable prices, good product quality and service quality are very necessary to be able to compete in the Indonesian market. Therefore, to get a broad picture of online transportation in Indonesia, this research aims to find out the influence of price, product quality and service quality on customer satisfaction for Maxim application users who live in Kelapa Gading, Jakarta. The sampling technique for this research was non-probability sampling, using purposive sampling to obtain a sample of 115 respondents. Data were processed using SPSS 25 and analyzed through descriptive statistics, classical assumption tests, and multiple regression analysis tests to determine the suitability of the model and the relationship between variables. The test results show that the three variables pass the classical assumption test. Data processing using multiple linear regression shows that Product Quality and Service Quality have a positive and significant effect on Customer Satisfaction.